Language Disorder of Autism In ‘Atypical’ Series (2017-2021): A Psycholinguistics Study - Mutiara Indah; Tika Yulianti (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this study is to recognize what kind of language disorder experienced by Sam as an autistic in ‘Atypical’ series 2017-2021, to describe what factors of language disorder experienced by Sam, and to describe what therapy of language disorder for Sam. The researcher uses qualitative method for doing this research. The data was taken from the utterances of autistic, Sam Gardner as the main character. There were 60 phenomenon of language disorder, 58 receptive language disorder and 2 expressive language disorder. The most common symptom of receptive language disorder experienced by Sam is difficulty following verbal directions 21 data, followed by interpreting words or phrases 19 data, not appearing to listen 12 data, limited vocabulary 3 data, difficulty understanding complex sentence 2 data, and demonstrating lack of interest 1 data. Meanwhile, Sam just experienced two symptoms of expressive language disorder, word-finding difficulties 1 data and over-reliance on stock phrases 1 data. This phenomenon occurs caused by many factors, whether difficulty in joint attention, failed in integrated the information with semantic attributes, autism symptoms such as echolalia, deficits in ToM, trouble in retrieval words, etc.